Building Resources in Caregivers: Feasibility of a Brief Writing Intervention to Increase Benefit Finding in Caregivers. Issue 2 (5th February 2020) - Gallagher, Stephen; O'Sullivan, Liam; Hughes, Zoe; O'Connell, Brenda H.
Abstract : The Building Resources in Caregivers (BRiC) is a pilot feasibility trial that compared the effects of a 2‐week benefit finding writing expressive intervention to a control intervention, who wrote about the weather. Caregivers completed primary (benefit finding) and secondary (quality of life, depression and anxiety) outcome measures at pre (t1), immediately post‐test (t2) and 1 month later (t3). They also completed measures relating to trial feasibility, difficulty, and acceptance. Using complete case analysis only, analysis revealed no effect of the intervention for primary or secondary outcomes. Despite this, there were no differences between the intervention and control groups on key feasibility measures. Caregivers in the control condition were less likely to recommend this to other caregivers. Moreover, qualitative commentary provided by caregivers suggested that not everyone enjoyed the writing, some found it stressful, offering up some explanation for our findings. Our pilot trial suggests that any future benefit‐finding writing intervention would require several procedure modifications including tailoring to a specific cohort of caregivers, in particular those who like writing, before it has some utility as a psychosocial intervention.